Analisis Pengaruh Pendalaman Sektor Keuangan dan Cadangan Devisa Terhadap Nilai Tukar Mata Uang Indonesia, Malaysia, dan Filipina - Kardina Siregar; Yuli Ariani; Rusiadi Rusiadi; Suhendi Suhendi; Lia Nazliana Nasution (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
This research aims to analyze the influence of financial sector deepening and foreign exchange reserves on currency exchange rates in Indonesia, Malaysia and the Philippines. The variables in this research are exchange rate, GDP, credit interest rates, money supply, foreign exchange reserves. This research uses secondary data taken from WorldBank in 2005-2022. The data analysis technique used is the Autoregressive Distributed Lag (ARDL) panel. The research results from the ARDL model analysis show that the countries that are able to become lead indicators for KURS tariff stability are Indonesia and Malaysia. This is because all the variables or indicators in the research, namely (Foreign Exchange Reserves, GDP, JUB and Credit Interest Rates) in these countries have a significant effect on the KURS, while CDV, GDV and JUB do not have a significant effect on the KURS. in the Philippines, only the SBK variable has a significant effect on the KURS in the Philippines. If we look at short-term and long-term stability, the Unemployment Rate variable, both short-term and long-term, has a significant effect on KURS stability.